A Brief Review on Image Contrast Enhancement Techniques - Titariya, Deepanjali; Pandey, Rajeev; Agrawal, Shikha (International Journal of Computer Sciences and Engineering, 2019)
In the field of image processing one of the important process is image enhancement. In many image processing applications, image enhancement techniques are used. Many research works have been done for image enhancement. In this paper, different techniques and algorithms using machine learning approach such as genetic algorithm, neural networks, fuzzy logic enhancement and optimization techniques are studied and discussed. The aim of this study is to determine the application of machine learning approaches that have been used for image enhancement. The review given in this paper is quite efficient for future researchers to overcome problems related to machine learning approach as well as helps in designing efficient algorithm which enhances quality of the image.